Kasus Penganiayaan Berat Mario Dandy Satriyo Terhadap Cristalino David Ozora - Rumahorbo, Liberti; Yusuf, Hudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The case of severe persecution committed by Mario Dandy Satriyo against Cristalino David Ozora shocked the Indonesian public. The incident was not only a legal concern, but also opened up criminological and social discussions regarding violence, abuse of power, and social inequality. This article discusses the background, legal process, as well as the social and legal impact of the case. Criminological and juridical analysis approaches are used to understand the causes and their implications as well as their prevention solutions in the future.